LEVEL OF BIOSECURITY IMPLEMENTATION IN CLOSED HOUSE BROILER CHICKEN FARMS IN SUSUT DISTRICT, BANGLI REGENCY, BALI - Luh Putu Manik Samitha Utami; I Ketut Suada; Nyoman Adi Suratma (Buletin Veteriner Udayana, 2024)
Biosecurity is a management step that must be taken by farmers to prevent disease germs from entering the farm and to prevent diseases on the farm from spreading to other farms. This research aims to determine the implementation and level of application of biosecurity components in closed house cages for broiler chicken breeders in Susut District, Bangli Regency, Bali. The method used is a census of respondents, namely all breeders. The data obtained from the interviews is tabulated and then the percentage of the amount of data that is in accordance with biosecurity implementation practices is calculated. The results show that overall farmers have implemented biosecurity components with each biosecurity component, namely the sanitation component showing the Very Good category (85%), the traffic control component showing the Poor category (38.81%) and the sanitation component showing the Very Good category. (97.7%). From the results obtained, chicken farmers should further improve their biosecurity implementation system, especially for guests/farm workers, because a very big factor in the spread of disease is the traffic component, including people, equipment and vehicles.